Inovação aberta em companhias de saneamento básico brasileiras - Vasconcelos, Etienne Unias de (2019)
The present study aimed to investigate how Brazilian sanitation companies that adopt open innovation perform the processes of this type of innovation. According to Chesbrough (2012), open innovation is the continuous flow of knowledge that expands when companies seek new sources of technologies in the market, as well as make their knowledge produced and developed internally available in the external environment. To achieve the proposed objective, companies that adopt open innovation were identified; the type of open innovation process adopted by companies was analyzed; It was also verified how companies carry out co-creation efforts; In addition, an analysis of the management of intellectual property was performed and the internal R&D performance of the companies was identified. The research used qualitative approach, being characterized as exploratory, having as strategy multiple case study. Semistructured interviews were conducted with thirty managers of the companies' R&D and water and sewage operating areas. The first result presented was the concept of open innovation in the perception of respondents: use of available knowledge through the formation of partnerships in order to obtain internal gains. Another result found points to eight principles of open innovation, three of which coincide with the principles of Chesbrough (2012): systematic capture of knowledge; conducive organizational arrangement and applicable and distributed knowledge. The other principles identified were expanded contribution, value creation, long-term vision, reduced costs, and customer focus. The results also showed that all the companies investigated adopt open-type innovation from the outside, according to the classification of Gassmann and Enkel (2004). Some companies (A, B and C), however, are in the transition phase between inbound open innovation and coupled innovation, which led to the classification into a new type of open innovation found in this study: semi coupled open innovation. The other companies (D, E and F) only embrace open innovation from the outside. From this perspective, it was observed the existence of two open innovation trajectories, not identified in the base literature of this study, within the investigated companies: Y trajectory (companies A, B and C) and linear trajectory (companies D, E and F). It was also found that co-creation efforts are mainly carried out with suppliers and universities, and prospecting for new ideas is done through practices such as benchmarking visits, congresses, technical meetings and meetings. Another result was the management of intellectual property that refers to the protection of new ideas through patents, but there are no policies and procedures capable of pointing and classifying the strategic ideas to be protected and / or made available. Regarding the R&D performance, the results point to the main roles of this area in the consolidation of open innovation in companies, namely: it acts as a facilitator, as an intermediary and as a diffuser engine of innovation. But some “blind spots” must be observed in driving open innovation within companies: organizational culture, translation of needs into measurable characteristics, and interaction with other areas of the company. The results of this study support the research carried out in other companies, as well as corroborate the highlighted literature and contribute to the deepening of studies on the subject.